Análisis Financiero al Comercial “MOTOS & MOTOS” de la ciudad de Loja, periodos 2019-2020. - Morocho Macas., Viviana Elizabeth (2022)
The curricular integration research work entitled "FINANCIAL ANALYSIS TO THE COMMERCIAL "MOTOS & MOTOS" OF THE CITY OF LOJA, PERIOD 2019-2020", has the aim of knowing the real situation of the company through a financial diagnosis that allows to know the economic and financial position; therefore, its owner makes appropriate decisions for the benefit of it. For purposes of accomplish the objectives, set out in this curricular integration research work, a preliminary visit was carried out and the application of a research instrument to obtain general and specific data of the entity and to obtain the necessary financial statements for the development of the corresponding analysis. Giving way to the realization of a vertical analysis establishing the degree of participation of each of the accounts in relation to the group and subgroup to which they belong, getting to know the economic and financial structure, in the same way a comparative analysis determines the increases or decreases of the figures that the accounts have had from one period to another as a result of the operations carried out in order to detect the reasons of such alterations and to be able to take corrective action in time. Consecutively, financial indicators were applied indicating the level of liquidity to generate cash and cover its short-term obligations, indebtedness to verify the level it has to borrow in the short and long term, the activity of the commercial through the rotation of inventories, period of permanence, and the terms of collection and payment as well as profitability to measure the effectiveness of controlling costs and expenses to determine the generation of returns that compensate for the investment generated. As a result, the static analysis showed that with significant participation the current assets represented were found with 96.17% and 77.51% with a value of $ 1,189,924.75 and $ 1,303,120.35 dollars respectively to the periods 2019-2020 due to their commercial activity concentrating their values in the inventory of merchandises, documents, and accounts receivable. Likewise, after the dynamic analysis it was shown that the bank account has had a representative decrease of 90.20% due to the purchase of merchandises and the partial payment of its obligations; while in the economic structure, the sales account has obtained a growth of 87.76% due to the adoption of home delivery service by motorized in most businesses after the health crisis, as well as the cost of sales with 62.02% due to the acquisition of new merchandise to maintain an updated stock in order to meet the existing demand. 5 Through the application of the financial indicators it was denoted that the entity has an adequate level of liquidity to cover the debts acquired, the stock rotation is limited since they are carried out every two or three times a year, the average collection days are 98 days which means that customers comply with their obligations late and therefore the entity complies with its suppliers on time, and with respect to profitability, the commercial has a use of the available resources generating profits in the periods in question through a satisfactory administration and performance in commercial operations, creating an added value and being profitable in the market. To conclude, a report of the financial analysis was made, it contains in a summarized form the results obtained, conclusions and recommendations on the financial economic situation of the Commercial "MOTOS & MOTOS" to provide guidelines for an adequate decision making focused on improving the management of economic and operational activities that ensure stability in the market.